Evaluating the impact of pattern recognition on AI skills development in universities - Kazimova, Dinara; Serikbayeva, Nurgul; Samashova, Gulfarida; Zatyneyko, Anatoly; Sarsenbayeva, Botagoz (Frontiers in Education, 2025)
Pattern recognition is a cornerstone of Artificial Intelligence (AI), shaping critical applications such as image analysis, speech processing, and automated decision-making. This study examines the impact of university curricula on developing AI competencies through dedicated pattern recognition training. A mixed-methods approach was employed to assess student comprehension, curriculum effectiveness, and challenges in mastering advanced concepts. The analysis reveals that structured coursework significantly enhances practical AI skills; therefore, recommendations include integrating more hands-on experiences and continuously updating course content. Such refinements promise to better prepare students for real-world challenges and industry demands. In conclusion, evolving instructional practices are essential for robust AI expertise.